Sonohysterography and sonohisterosalpingografía - Quispe, José (2015)
OBJECTIVE: To evaluate the usefulness of sonohysterosalpingograpby in the diagnosis of the uterine cavity and tubalpatency. MATERIAL: Prospective study of 76 women with diagnosis of abnormal endometrium infertility. RESULTS: Sonohysterosalpingography is a good method for the diagnosis of polyps, submucosus or intramural myomas. It is a good, fast, low cost ambulatory procedure.